Implementasi Rules dan Manajemen Bandwidth pada Mikrotik di Perumahan Permata Puri Harmoni RW 016 - Tri Wahyudi; Adi Riswan; Fath Maulana; Dennis Andika Putra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Using rules with bandwidth management improves network utilization and optimizes system performance. By prioritizing network access, you can better manage bandwidth usage and thus better serve applications that require higher bandwidth. Additionally, rules help you maintain network security by identifying and managing unwanted activity such as piracy and virus spreading. Overall, this journal shows that the use of rules in Mikrotik's bandwidth management improves network efficiency and security. The bandwidth management method implemented is simple queuing with a maximum bandwidth of 10 Mbit/s for each user and network optimization by blocking websites with harmful content Permata Puri Harmoni Housing RW 016 Internet network stability.